CORRUPTION AND THE NIGERIAN ECONOMY: A DESCRIPTIVE SURVEY OF INHIBITING BEHAVIORAL FACTORS (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
It has been observed by scholars and commentators that corruption is a major challenge to social, political, and economic development in any country. The con- sequences of corruption are unfavorable for the progress of any society. Against this backdrop, this article examines the effects of corruption on the economic development of Nigeria. It discusses the sociocultural, political, and economic factors responsible for the endemic nature of corruption in Nigeria and concludes that the “top-to-bottom” corruption in Nigeria has negatively affected the country’s economic development. To change this situation, the leadership must genuinely commit to fighting corruption from the top down; corruption control mechanisms need to be strengthened, the offenders need to be punished, and the citizenry needs to be mobilized to demand transparency and accountability.